Hell within hell : sexually abused child holocaust survivors ; the comorbidity of the traumata - Lev-Wiesel, Rachel; Weinger, Susan (Univ. Pr. of America, 2011)
Introduction -- The continuing influence of early trauma -- Childhood sexual abuse -- Marina -- David -- Condolisa -- Judith -- Cornelia -- Dunia -- Tova -- Afterword